Al2O3 obtained through resistive evaporation for use as insulating layer in transparent field effect transistor - Boratto, Miguel Henrique [UNESP]; Scalvi, Luis Vicente de Andrade [UNESP]; Machado, Diego Henrique de Oliveira [UNESP] (Trans Tech Publications Ltd, 2014)
Alumina thin films have been obtained by resistive evaporation of Al layer, followed by thermal oxidation achieved by annealing in appropriate atmosphere (air or O-2-rich), with variation of annealing time and temperature. Optical and structural properties of the investigated films reveal that the temperature of 550 degrees C is responsible for fair oxidation. Results of surface electrical resistivity, Raman and infrared spectroscopies are in good agreement with this finding. X-ray and Raman data also suggest the crystallization of Si nuclei at glass substrate-alumina interface, which would come from the soda-lime glass used as substrate. The main goal in this work is the deposition of alumina on top of SnO2 to build a transparent field-effect transistor. Some microscopy results of the assembled SnO2/Al2O3 heterostructure are also shown.
Keywords: Alumina; Resistive evaporation; Thermal annealing; Oxidation